Histological, immunohistochemical, and morphometric analysis of negative pressure-assisted in-vivo nerve stretch-growth. (21st June 2022) - Sana Ullah Sahar, Muhammad; Mettyas, Tamer; Shah, Megha; Bindra, Randy; Barton, Matthew
Highlights: In-vivo stretching of a nerve using negative pressure increases its growth rate. A positive correlation exists between nerve growth and applied in-vivo strain. Abstract: Axons respond well to mechanical stimuli and can be stretched mechanically to increase their growth rate. Although stretch growth of axons and their transient lengthening ex-vivo has been discussed in literature extensively, however, real applications of this phenomenon are scarcely found. This work presents a technique to translate ex-vivo axonal stretch growth to in-vivo nerve stretch growth. By establishing a rat model of completely transected sciatic nerve injury, the regrowth rate of the proximal nerve stump was examined under the effect of a stretching force developed by negative pressure. In this manuscript, results have been presented based on quantitative and qualitative analysis of the stained nerve tissues. Gross observations have explicitly confirmed that the proximal stump of a whole sectioned sciatic nerve of a Wistar rat stretched in a T-shaped nerve prosthesis using a controlled amount of negative pressure displayed a better outcome in terms of an increase in the total length of proximal nerve stump post-treatment and a higher number of blood vessels with respect to control. The histological and morphometric analyses confirmed that negative pressure-assisted nerve growth provides an alluring control over nerve's regrowth rate. Immunohistochemical staining also supported the existence of a positive correlation between nerve growth and in-vivo application of axial stress on it. This work presents the first holistic evidence on growing nerves in the continuum of in-vivo nerve stretch growth using negative pressure and concludes that systematic and controlled negative pressure applied directly to the resected ends of a sciatic nerve resulted in the enhanced growth rate of regenerating nerve fibres.